Entornos de programación no mediados simbólicamente para el desarrollo del pensamiento computacional. Una experiencia en la formación de profesores de Informática de la Universidad Central del Ecuador - Pérez Narváez, Hamilton Omar; Roig-Vila, Rosabel (Revista de Educación a Distancia (RED), 2015)
The present paper focuses on the research carried out with students in the first semester of the Computer Science Degree, at the Faculty of Philosophy, Letters and Education Sciences of Ecuador Central University, seeking to analyze the utilization of non-symbolically mediated programming environments as a teaching tool for the development of computational thinking. The aim sought is to identify the potential advantages of applying the aforesaid non-symbolically mediated programming environments for students to develop computational thinking skills such as creativity, modeling and abstraction, amongst others, which are important in programming. The research was supported on a mixed methodology, with field research and documentary research at a descriptive level. A questionnaire served to collect data from the Degree students. Finally, after gathering all the information, data processing took place following descriptive statistics criteria through which conclusions and recommendations can be reached.